Fullmetal alchemist. Vol. 23 - Arakawa, Hiromu, 1973-; Forbes, Jake (VIZ Media ; Simon & Schuster [distributor], 2010)
"As the battle for Central City rages on, Alphonse faces off against Pride and Kimblee with the aid of a Philosopher's Stone. Can he come up with a plan to take down these two dangerous foes? Meanwhile, Ed and his friends run into Envy below the city. When Roy Mustang learns the truth about Hughes's murder, will he be consumed by hatred and do the unthinkable?"--Publisher's web site.